1997
DOI: 10.1088/0953-8984/9/5/005
|View full text |Cite
|
Sign up to set email alerts
|

A new technique to calculate the electronic structure of two-dimensional disordered systems

Abstract: The purpose of this work is to investigate the electronic structure of two-dimensional structurally disordered solids by means of a method based on multiple-scattering theory. The theoretical technique is applied to some two-dimensional models which can be varied from the limit of a perfect to a completely disordered structure. The models are continuous structural networks with different-fold coordinations of atoms in planar structures. The spectral density is determined through a self-consistent approach. Usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2005
2005

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 13 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…However, it should be emphasized that the results do not depend on the potential in the extreme tightbinding limit because the total number of states in the band equals one per atom. We shall take appropriate values for atomic parameters such as the strength of the potential, as was done in the previous calculations [17,19]. For example, r = 0.5 (au) and the bond length between two atomic potential centres R = 2.0 (au), for which the ground state energy E 0 = −30 (au).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, it should be emphasized that the results do not depend on the potential in the extreme tightbinding limit because the total number of states in the band equals one per atom. We shall take appropriate values for atomic parameters such as the strength of the potential, as was done in the previous calculations [17,19]. For example, r = 0.5 (au) and the bond length between two atomic potential centres R = 2.0 (au), for which the ground state energy E 0 = −30 (au).…”
Section: Resultsmentioning
confidence: 99%
“…Hence, these calculations demonstrated that the approach can be used to calculate the DOS for systems having different hopping integrals and concentrations if the bandwidth is much greater than the spread of binding energies. In one sense such systems are also some kind of disordered system having different bond distances between atoms and consisting of sublattices like the Fibonacci lattice in two dimensions [19,26].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations